Preclinical Students’ Views on Medical Ethics Education: A Focus Group Study in Turkey - Can Bilgin, Ahmet; Timbil, Sevgi; Huseyin Guvercin, Cemal; Ozan, Sema; Semin, Semih (Acta Bioethica, 2018)
Aim: We aimed to receive the opinions of the preclinical medical students on medical ethics education, and to present some suggestions for the education program. Methods: Focus group discussions were held with third-grade medical students. The analyses were implemented using Creswell’s six-step qualitative data analysis. Results: During the data analysis, themes with the following titles were identified: necessity of the education, content, education methods, assessment, participation, contribution of the education, moving to clinical training and suggestions. Discussion: The students stated that the discussions on movies/books/case-based scenarios are more useful than lectures. Although they believed that student assessment was necessary for the medical ethics education, they had negative attitudes towards Multiple Choice Questions. At the stage of moving to the clinical training, their feelings and thoughts about the learning outcomes they would gain from ethical education were contradictory. Conclusion: Each theme and code obtained from the students’ expressions may contribute to improving medical ethics education for all institutions. Besides student education, it is also necessary the faculty development programs on medical ethics education for clinical teachers. Additionally, further studies can be conducted on the actions that need to be taken to help students internalize the ethical issues and feel the need of learning more.